Riesgo suicida asociado a niveles de calidad de vida de estudiantes. Universidad Nacional de Chimborazo. Riobamba, 2021 - Karen Leonela, Acosta Lalaleo (2021)
ABSTRACT The main objective of the present research was to analyze the suicide risk associated with levels of quality of life in students of the National University of Chimborazo. Riobamba, 2021. The methodology had a quantitative approach, of a bibliographic and field type, with a cross-sectional design, of a descriptive level. The study population comprised 111 subjects from the first, second, and third semesters of the Clinical Laboratory of the National University of Chimborazo. The questionnaire technique and psychological reagents were used, the following instruments were applied: Plutchik's Suicidal Risk Scale (ERSP) and the GENCAT Scale. Among the most relevant results, it was evidenced that 27.9% of the participants present suicidal risk, concerning the quality of life, a predominance of low levels was found in the dimensions of Material Well-being, Physical B, and Rights. Finally, Concerning the overall Quality of Life, 55% of the students present a low level, which indicates that they sustain a poor quality of life. A psychoeducational guide was developed to provide activities focused on preventing suicide risk and improving quality of life. Keywords: university students, suicide risk, quality of life. Reviewed by: Mgs. Lorena Solís Viteri ENGLISH PROFESSOR c.c. 0603356783